Prioritizing the efforts: lived experiences of family when taking care of people with cancer† - Ligita Titan; Andriani Merry; Hazwani Hazwani; Fransiska Ersy Aprilya; Aulya Shafira (Sciendo, 2023)
Cancer has one of the highest disease mortality rates. Families are very important in the treatment of people with cancer. By using a phenomenological design, this study aimed to explore the experience of families in caring for a person with cancer and to identify the needs of these families.